A Stubborn Culture? Zimbabwean Migrants and the Quest for a Decent Burial during the Covid-19 Pandemic. Issue 2 (3rd July 2021) - Hungwe, Chipo
Abstract: The rise in deaths due to the combined effects of the Covid-19 pandemic and other communicable and non-communicable diseases has made it difficult for Zimbabweans to dignify death and offer decent burials to the deceased. Funeral parlours and other players in the death industry have become overwhelmed. This article explains the behaviour of Zimbabweans in the diaspora who continue to repatriate dead bodies into the country even when repatriation poses challenges to all involved, especially during the Covid-19 pandemic. Concepts such as "the living dead", "death in and out of place", and "good death versus bad death" are used to analyse perceptions of death among Zimbabweans. For the Shona and Ndebele (the biggest ethnic groups in Zimbabwe), the living and the dead form part of the same community. Repatriation of the dead is an attempt to dignify death and offer a decent send-off to the deceased, whose spirit must be placated lest they become vengeful. Burial location signifies an affirmation of belonging to the kin group. The grave site, and its accessibility, gives kin members the opportunity to perform the necessary rituals at any time.